Hodgkin Lymphoma : A Comprehensive Overview - Engert, Andreas; Younes, Anas (Hematologic Malignancies, 2015)
This book examines in detail the current treatment options for first-line, relapsed, and refractory Hodgkin lymphoma and the management appropriate in special clinical circumstances, including in the elderly, pregnant women, and those with lymphocyte-predominant disease. Careful attention is devoted to the emerging individually tailored treatment strategies that are especially appealing given their potential to reduce early and late treatment side effects in this generally young patient population. In addition, clear guidance is provided on the management of Hodgkin survivors. Other topics addressed include epidemiology, pathogenesis, the role of the microenvironment, initial clinical evaluation, imaging diagnosis, use of staging systems, and prognostic factors. The second edition of Hodgkin Lymphoma: A Comprehensive Overview has been revised and updated by the key opinion leaders to reflect recent progress in the field. It will be of great value to hematologists, oncologists, and all others with an interest in Hodgkin lymphoma. .